A comparative study of American, Japanese, and Taiwanese early childhood teachers' perceptions of clean-up time. (June 2017) - Izumi-Taylor, Satomi; Ito, Yoko; Lin, Chia-Hui; Akita, Kiyomi
The purpose of this study was to examine similarities and differences of American, Japanese, and Taiwanese kindergarten teachers' perspectives about clean-up time. The participants consisted of two female American kindergarten teachers in the southeastern US, two female Japanese kindergarten teachers on the main island, and two female Taiwanese kindergarten teachers from central Taiwan, all of whom teach four-year-olds. Qualitative analysis of the data yielded four themes regarding teachers' views of clean-up time: teaching cleaning-up methods, the developmental stages, the extension of play, and reflection of one's own practical knowledge and skills. These teachers perceived clean-up time was more than just a transitional time. The implications for early childhood education are presented.